1995
DOI: 10.1007/bf00191221
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of V genes: DNA sequence structure of functional germline genes and pseudogenes

Abstract: In this review we have examined the features of germline sequences of IgV genes from a number of species in an attempt to identify the "signature" of molecular mechanisms responsible for generating and maintaining diversity in the germline repertoire (after gene duplication by meiotic unequal crossover). We now summarize the relevant features point by point: 1. Codon analysis reveals a significant deficit of stop codons below the numbers that would be expected under random point mutational change. This implies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 58 publications
(115 reference statements)
1
38
0
Order By: Relevance
“…In chicken, IglV and IghV pseudogenes have been identified that include crippling mutations (182). However, only a few IglV and IghV pseudogenes contain more than one crippling mutation and, notably, very few are crippled because of stop codons or frameshift mutations.…”
Section: Evolutionary Conservation Of Pseudogenesmentioning
confidence: 99%
“…In chicken, IglV and IghV pseudogenes have been identified that include crippling mutations (182). However, only a few IglV and IghV pseudogenes contain more than one crippling mutation and, notably, very few are crippled because of stop codons or frameshift mutations.…”
Section: Evolutionary Conservation Of Pseudogenesmentioning
confidence: 99%
“…(50) have argued that Ig V region genes cannot be under direct positive selection favoring diversity at the amino acid level. They base their argument on the fact that somatic hypermutation serves to diversify these molecules further; thus the germline sequence does not directly encode the final protein product.…”
Section: Gene Duplicationmentioning
confidence: 99%
“…It has been reported recently (for review, see that synonymous point mutations occur far more frequently than do nonsynonymous base changes in the Drosophila Est-6 pseudogene . In chickens, it has been observed that, within the multiple IglV and IghV pseudogenes, the number of stop codons contained in the ''coding'' sequence is far lower than would be expected were nucleotide substitutions occurring at random; in addition, the majority of stop codons introduced by point mutations are then ''corrected'' and eliminated by further point mutations within the same codon (Rothenfluh et al 1995). This feature, which is also observed in V H pseudogenes in mice (Schiff et al 1985), may indicate either that some presumed pseudogenes are, in fact, protein-coding, or that the conservation of open reading frames plays a role in any putative function of pseudogenes involved in somatic gene rearrangements .…”
Section: Evolution and Conservation Of Pseudogenesmentioning
confidence: 99%